Kemal Tahir ve Yaşar Kemal Örnekleri Üzerinden Eşkıyalık Yazımına Bir Bakış - Topluk, Gökhan (Muş Alparslan Üniversitesi, 2017)
In this study, as a fundamental problem in the writing of banditry, it is aimed to draw attention to the contradictory contents of the rebelled bandit in the state records and to the perception of the social bandits in the folklore. A theoretical ground on how Yaşar Kemal and Kemal Tahir have a methodological preference in the context of banditry have been tried to be established by mentioning some names which can be examples for the discussions of historical reality of these two materials that can be used by those who will work in this field. Moreover, it was tried to discuss the view of two of our writers about the folklore and folk poets and the view of Kemal Tahir about state phenomenon in terms of banditry.

Bu çalışmada eşkıyalık yazımında temel bir problem olarak devlet kayıtlarındaki asi/şaki eşkıya ile folklordaki sosyal eşkıya algısının birbirine zıt muhtevasına dikkat çekilmek istenmiştir.  Bu sahada çalışacak olanların malzeme olarak kullanabileceği bu iki materyalin tarihi gerçekliğine dair tartışmalara örnek teşkil edecek bazı isimler zikredilerek Yaşar Kemal ve Kemal Tahir’in eşkıyalık bağlamında nasıl bir metodolojik tercihte bulunduklarına dair kuramsal bir zemin oluşturulmaya çalışılmıştır. Ayrıca yine eşkıyalık üzerinden söz konusu iki yazarımızın folklor ve halk şairlerine, Kemal Tahir’in ise devlet olgusuna bakışı tartışılmaya çalışılmıştır.
Analysis of Banditry Writing with the Examples from Kemal Tahir and Yaşar Kemal
anemon
Keywords: Bandit; Kemal Tahir; Yaşar Kemal; Folklore; State; Bards; Kemal Tahir; Yaşar Kemal; Folklor; Devlet; Saz Şairleri; Eşkıya; Saz Şairleri